Essential home skills handbook : everything you need to know as a new homeowner - Peterson, Chris, 1961- (Cool Springs Press, an imprint of The Quarto Group, 2022)
Whether you're moving from an apartment to your first home or you're inspired to tackle a particular home project, we're glad you're here! If you've decided it's time to fix that dripping faucet or a small gutter leak before it becomes a big problem, let's get to it.